Characterization of Staphylococcus aureus Isolates From Cases of Clinical Bovine Mastitis on Large-Scale Chinese Dairy Farms - Kangjun Liu; Kangjun Liu; Kangjun Liu; Luyao Tao; Luyao Tao; Luyao Tao; Jianji Li; Jianji Li; Jianji Li; Li Fang; Li Fang; Li Fang; et al. (Frontiers in Veterinary Science, 2020)
Bovine mastitis is a prevalent disease that causes serious economic problems globally in the dairy industry. Staphylococcus aureus is an important pathogen of bovine mastitis. This study was conducted to characterize S. aureus isolates from clinical bovine mastitis cases in large-scale dairy herds in China. S. aureus was isolated from 624 clinical mastitis cases and confirmed by matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS). In total, 62 S. aureus isolates were obtained. Cluster analysis, genetic diversity, quantification of biofilm formation, antimicrobial resistance, and detection of virulence genes were performed on these isolates of S. aureus. Eight isolates harbored the mecA gene and were sensitive to oxacillin. MALDI-TOF MS cluster analysis revealed that the 62 isolates were divided into three major clusters (I, II, III) and eight main groups (A–H) at the distance level of 700. The agr II was the most prevalent (56.5%). The 62 S. aureus isolates were assigned to seven spa types. The most common spa type was t529(58.1%), followed by t2196 (14.5%), t518 (14.5%), t571(6.5%), t034 (3.2%), t2734 (1.6%), and t730 (1.6%). Five STs were identified from seven representative isolates as follows: ST630/CC8, ST97/CC97, ST50, ST398, and ST705. All isolates had the ability to form biofilm. Antimicrobial resistance was most frequently observed to ciprofloxacin (29%), followed by penicillin (24.2%), and streptomycin (9.6%). All isolates harbored the fnbA, clfB (100%), icaA, and icaD genes. This study provides the basis for the development of bovine mastitis prevention program on large-scale dairy farms.